Pedestrian Arrangement On Wr Soepratman Street Bengkulu City as an Educational Area - Juwito, Rizqiyah Safitri; Fatona, Geby; Sari, Renitha (MultiTech Publisher, 2024)
Urban development is one of the forms of progress of a city, which shows that the economy of an area is running well, especially in the education area. The education area is an area that has a level of density at a certain time span and provides facilities for pedestrian space. A good educational area is to provide ease of movement for pedestrians. However, this is rarely found in the education area. Education areas are more dominated by the economy in the form of trade and services, so the need for pedestrian ways is often forgotten and considered unimportant. This can be seen on Jalan WR Soepratman (the gate of Bengkulu University (UNIB) up to Elementary School 69 Bengkulu City. Every day, Jalan WR Soepratman is high in motorized vehicle and pedestrian activity, both from students and from the community. The high level of activity in the area along WR Soepratman is due to the large number of Bengkulu University students and students from 69 Bengkulu City elementary schools. On the WR Soepratman road that connects Bengkulu University (UNIB) with Elementary School 69 Bengkulu City, there are no pedestrian facilities. On the shoulder of the road is used for selling activities for street vendors. Based on this, research is needed so that the end of this research can be a design solution in planning pedestrian paths on WR Soepratman Road. The research methods used are literature study, observation study, and descriptive analysis.